TOPONIMI KECAMATAN DI KABUPATEN JEMBER - Wardatul Jannah; Nina Sulistyowati; Arum Jayanti (Widyaparwa, 2021)
This research discusses the linguistic forms, meanings, and socio-cultural aspects of sub-district toponymy in Jember. The study is qualitative research. The data were the subdistrict names in Jember taken from the official website of Jember Regency. The data were classified based on their lingual units. Furthermore, the sub-district names in Jember were analyzed with semantic analysis. The last analysis was the identification of the socio-cultural aspects behind the sub-district names. There are 3 results of sub-district names analysis in Jember: (1) the form of linguistic units of the sub-district names in Jember are monomorphemic words, polymorphemic words (affixation, compound words, and affixed compound words), and a lexeme consisting of two morphemes, (2) the meanings and categorizations of the sub-district names in Jember are based on the manifestation aspects in the form of water, the appearance of the earth, flora, and fauna, (3) the socio-cultural aspects behind subdistrict naming in Jember are cultural and habitual patterns, prayers and hopes, and folklore. Penelitian ini membahas bentuk kebahasaan, makna, dan kategori toponimi kecamatan di Kabupaten Jember. Penelitian ini merupakan penelitian kualitatif. Data pada penelitian ini adalah nama-nama kecamatan di Kabupaten Jember yang bersumber dari laman resmi Kabupaten Jember. Data berupa nama-nama kecamatan kemudian diklasifikasikan berdasarkan satuan lingualnya. Selanjutnya, dilakukan analisis semantis pada nama-nama kecamatan di Kabupaten Jember. Analisis yang terakhir adalah pengategorian toponimi berdasarkan aspek-aspek yang melatarbelakangi penamaan kecamatan tersebut. Dari data nama kecamatan di Kabupaten Jember ditemukan dua hal: (1) bentuk satuan kebahasaan nama kecamatan di Kabupaten Jember, yaitu berupa kata monomorfemis, kata polimorfemis (afiksasi, kata majemuk, kata majemuk berafiks) dan leksem yang terdiri dari dua morfem), (2) makna dan kategorisasi nama kecamatan di Kabupaten Jember yang didasarkan pada aspek-aspeknya, yaitu aspek perwujudan berupa wujud air, rupa bumi, flora, fauna dan aspek sosial budaya yaitu, pola budaya dan kebiasaan, doa dan harapan, serta cerita masyarakat.